Speech and beatboxing cooperate and compromise in beatrhyming - Blaylock, Reed; Phoolsombat, Ramida; Mullady, Kaila (Frontiers in Communication, 2023)
Beatrhyming is a type of multi-vocalism in which an individual beatboxes and speaks (i.e., sings or raps) at the same time by interweaving beatboxing sounds and speech sounds within words and phrases. The measurements in this case study of a beatrhyming performance focus on one-to-one sound “replacements” in which a beatboxing sound is integrated into a word by taking the place of a speech sound. The analysis unfolds in two parts: first, a count of how many times beatboxing sounds used in place of speech sounds matched the intended speech sounds for vocal tract constrictor and constriction degree; and second, an assessment of whether the beatboxing sound patterns in beatrhyming (beatboxing with simultaneous lyrics) have the same degree of rhythmic structure as the beatboxing sound patterns in beatboxing (without lyrics). Despite having disparate aims, the separate speech and beatboxing systems work together to create a well-organized combined behavior. Speech tasks (i.e., communicating the linguistic message of the lyrics) are achieved in beatrhyming by replacing some speech sounds with beatboxing sounds that match the speech segment in vocal tract constrictor and in manner/constriction degree. Beatboxing tasks (i.e., establishing a musical rhythm) are achieved through the inviolable use of Outward K Snares K on the backbeat. Achieving both of these aims in the same performance requires flexibility and compromise between the speech and beatboxing systems. In addition to providing the first scientific description and analysis of beatrhyming, this article shows how beatrhyming offers new insight for phonological theories built to describe spoken language.